Gestational Syphilis: epidemiological impact in Maranhão state, Brazil - Verde, Roseane Mara Cardoso Lima (2020)
The present study aimed to trace the epidemiology of gestational syphilis in the state of Maranhão from 2012 to 2017, describing the age group, the diagnostic method, the clinical classification that most affects pregnant women, the time of diagnosis of positive cases of congenital syphilis. and the realization of prenatal care. In a quantitative approach, the research used as data source, the National System of Disorders and Notifications (SINAN). The parameters of age range, clinical classification of the disease, treponemal and non-treponemal test were observed. In cases resulting from congenital syphilis, prenatal care was evaluated, and the time of diagnosis of gestational syphilis in these cases. According to the data obtained, 4090 cases of gestational syphilis were reported in the period between 2012 and 2017, where 2873 represent women with the disease aged 20-39 years. The clinical diagnosis of primary syphilis is higher in all years analyzed. Regarding prenatal screening (VDRL), it was found that 84.4% of positive serologies were identified in the first test, however after the confirmatory test, 57.8% had positive results. There was an increase in the incidence of gestational syphilis cases in the years analyzed, with only a fall in 2016. Of the cases evaluated that resulted in congenital syphilis, 79.3% of women report having had prenatal care, most of them diagnosed. At this time and most of them at the moment of childbirth, demonstrating a problem in the state's primary health care.